The eloquence of the style of submission and delay in Verses of Heaven and Hell in the Holy Quran (Journal of the College of Basic Education, 2023)
Achieve the method of introduction and delay in the verses of heaven and hell - through its different stylesAnd its various contexts - great rhetorical connotations and meanings such as interest, care, suspense,And others, and the purpose of specialization that secures the soul has been manifested in a large and clear mannerThe believer is what she aspires to prove the reward for her good deeds. Add toExposing him to the villagers whose feet slipped off the straight path.The eloquence of the method of submission and delay:The method of introduction and delay is independent in the verses of Paradise; Fire has a high rhetorical statusIt is a unique stylistic phenomenon that alerts the reader's attention to the fact that submission and delay are an effective tool for highlightingThis intricate method, for every word was presented to one person and another was delayed for another matter.Sibawayh said in his book: (It is as if they give priority to the one whose explanation is more important to them, and they are exempt from his statement.They were all concerned and concerned about them) Tha.And it - without a doubt - includes exquisite rhetorical subtleties and precise meanings that participate in itPointing out the evidence, in addition to clarifying the meaning of the speaker behind the use of this methodThe funny rhetorician.Al-Zarkashi referred to it by saying: (It is one of the methods of rhetoric, because they brought it as evidenceon their mastery of eloquence and their ability to speak; and his submission to them; And he has the best location in hearts;